FAKTOR RISIKO KEJADIAN STUNTING PADA BALITA - Kusumawardani, Emi; Iswati, Ning; Assagaff, Farha; Noviani, Auliarinda (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Stunting is a condition of growth failure that occurs due to nutritional deficiencies during the critical period of the first 1,000 days of life (HPK), starting from pregnancy until the child is two years old. The purpose of this study was to determine the risk factors for stunting in toddlers. The research design used in this study was cross-sectional. The study was conducted at the Pahandut Community Health Center (BLUD UPT Puskesmas Pahandut). The study was conducted in January 2025. The study population consisted of all mothers with children aged 12-24 months. The study sample consisted of 50 respondents. The sampling technique used was purposive sampling. The research instrument used a research questionnaire. Data analysis was performed using univariate and bivariate methods. The results showed a relationship between income (p value: 0.00) and feeding patterns (p value: 0.004) with stunting. It is recommended that the Community Health Center improve crosssectoral cooperation with cadres and other health workers in preparing mothers with toddlers to be able to provide proper feeding patterns and prevent stunting, as well as to health workers, especially midwives, so that they can subsequently take a better approach in providing knowledge and information about proper feeding patterns and stunting prevention to mothers with toddlers aged 24-59 months. Keywords: Toddlers, Income, Feeding Patterns, Stunting.